Efficient conversion of tea residue nutrients: Screening and proliferation of edible fungi - Yufei Zhang; Yanyin Lu; Dandan Pan; Yanyan Zhang; Chen Zhang; Zexin Lin (Current Research in Food Science, 2024)
Despite lignocellulose hindering the extraction of intracellular components, tea residue can serve as an excellent substrate for fungal fermentation owing to their lignocellulose-degrading abilities. Thus, the fermentation efficiencies of Lentinus edodes, Lentinus sajor-caju (Fr.), Flammulina filiformis, Hericium erinaceus, Pleurotus pulmonarius, and Monascus kaoliang B6 were evaluated using tea residue as a medium. P. pulmonarius and L. sajor-caju (Fr.) exhibited the fastest growth rates, with colony radii of 33.1 and 28.5 mm, respectively. M. kaoliang B6 demonstrated substantial degradation abilities for cellulose, hemicellulose, and lignin, with decolorization radii of 12.2, 0.9, and 8.5 mm, respectively. After a 9-days liquid fermentation, M. kaoliang B6 achieved the highest conversion efficiency at 27.8%, attributed to its high cellulase (191 U∙mL−1) and lignin peroxidase (36.9 U∙L−1) activities. P. pulmonarius and L. sajor-caju (Fr.) showed lower conversion rates of 8.6% and 3.8%, despite having high hemicellulase activities (67.1 and 70.9 U∙mL−1). Fermentation by M. kaoliang B6 resulted in a reduction of protein and total sugar content in the tea residue by 174 and 192 mg g−1, by which the mycelium's protein and total sugar content increased by 73 and 188 mg g−1. Co-fermentation of these three strains had little effect on the improvement of conversion efficiency, which might owe to the antagonistic interactions among the strains. Generally, utilizing tea residue for edible fungi fermentation is a sustainable process for bio-waste treatment, enabling efficient nutrient conversion under mild conditions without adding chemicals.